Growth of banking - Poole, John (My University, 1896)
Introduction: Banking is about as old an industry as is known, reaching back in history through the Romans, Greeks, Phoenicians, and Florentines, and even biblical history records acts of usury. In primitive times when man produced everything he used, and there was no exchange between individuals, banks were useless and would have been of no advantage, hence they were not thought of. As industry became diversified and each man was no longer an organism of industry within himself, barter became the first means of exchange but as it was a very awkward method it soon gave place to a medium of exchange by which trades could be made easier and also at a great distance. How to facilitate there exchanges, it became necessary that the bank should be originated.
Citation: Poole, John. Growth of banking. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Banking; Biblical history; Exchange; Trades; Theses; Manuscripts (documents)